Broader Product Line: A Necessity to Achieve Success? - Kekre, Sunder; Srinivasan, Kannan (Management Science, 1990)
Strategic product line breadth decisions evoke differential responses from the manufacturing and the marketing areas: manufacturing prefers keeping process disruptions to a minimum and, as a result, discourages product proliferation; however, marketing, in its attempt to match products to heterogeneous consumer needs and gain market share, emphasizes a broader product line. We systematically investigate the market benefits and cost disadvantages of broader product lines on a large sample of over 1,400 business units. Our results indicate significant market share benefits and increases in firms' profitability with broader product lines; moreover, widely held beliefs of increases in production costs are not empirically supported. American manufacturing firms may indeed be flexible enough to accommodate product variety without significant detrimental effects on costs.